Altitude is positively correlated to race time during the marathon - Lara, B.; SalineroJ. J.; Del Coso, J. (High Altitude Medicine & Biology, 2014)
Completing a marathon (42.2?km) is one of the more challenging sports activities. Besides the distance, the ambient conditions of the race (altitude, temperature, etc) can increase the physiological demands of the event. The purpose of this study was to investigate the relation between the altitude of the city in which the marathon is held and the marathon race time. For this purpose, we sought the race times of 16 popular marathons performed at different altitudes above sea level (range from ˜0 to 2800 meters above sea level). In these competitions, we analyzed the race times of the female and male runners who finished from 21st to 100th position. We excluded the top 20 male and female finishers from the analysis because elite athletes usually compete in marathons held at low altitudes above sea level. Ambient temperature, the positive cumulative elevation gain, and the number of participants were used as control variables. Finishing time in the marathon was positively correlated with the altitude of the competition for both male (r=0.78; p<0.05) and female participants (r=0.73; p<0.05). On average, each increase of 1000 meters above sea level augmented marathon race time by 10.8±0.6% in men and 12.3±0.7% in women. Compared to race times in the Rotterdam marathon (held at 0 meters above sea level), the time taken to complete the marathon was significantly higher in competitions held at an altitude of over 700 meters. In conclusion, the time taken to complete a marathon strongly depends on the altitude of the city in which the marathon is held. Selecting marathon competitions close to 0m above sea level is a good strategy to maximize marathon performance.